THE EFFECT OF LIQUIDITY RATIO, PROFITABILITY SOLVENCYON STOCK PRICE IN CONSTRUCTION AND BUILDING COMPANIES LISTEDON INDONESIA STOCK EXCHANGE PERIOD 2014-2018 - Yurika Sepindo; Suhendro; Yuli Chomsatu (Jurnal Ilmiah Akuntansi dan Manajemen, 2021)
The development of infrastructure will certainly have a positive impacton share holders, it is reflected by government support by raising funds for infrastructure development. The seopportunities will certainly affect the price of shares in the property sector including financial performance. Financial performance can be seen from several financial ratios : liquidity ratio, profitability, and solvency. Sample in this study asmanyas 8 companies for 5 years sothatin 40 samples. The result soft his study simultane ouslyal variable sin this study we reaffected by the stock price. Partial liquidity variables (CR) donot affect the stock price, profitability (ROA) and (ROE) donot affect the stock price, solvability (EPS) affects the stock price, while DER does not affect the stock price.